Application of Coffee Flavor in Making Cookies with Uwi Flour Substitution at Pondok Rumah Sajada Sleman Yogyakarta: Aplikasi Flavor Kopi pada Pembuatan Cookies dengan Substitusi Tepung Uwi di Pondok Rumah Sajada Sleman Yogyakarta - Siti Tamaroh; Yuli Perwita Sari; Tyastuti Purwani (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Arabica coffee milling is one of the business units run at Pondok Rumah Sajada Sleman, Yogyakarta. Its use is still limited to selling ground coffee products or as an ingredient in coffee drinks at local drink shops. Therefore, the potential of this coffee needs to be developed more widely and have a selling value like cookie products. Cookies are a food product that is very familiar to the public. The light texture, flavors, and aromas that can be developed in various ways make the trend of cookie consumption even more attractive. On the other hand, students in Islamic boarding schools need to be equipped with knowledge related to food product processing, which can later become a provision for their future independence. In this service activity, socialization, and the practice of applying coffee flavor to making cookies with the substitution of purple uwi flour have been carried out at the cottage. Apart from utilizing the existing potential of ground coffee, coffee can increase consumers' attraction to cookies. The activity method is carried out using lecture techniques, which are equipped with the distribution of posters to each student and the practice of making cookies together. The boarding school administrators and students appreciated the positivity of this activity. This activity can be further developed by making other low-calorie cookies and business management training for students.